A hybrid demand-side policy for balanced economic emission in microgrid systems - Singh, Arvind R; Dey, Bishwajit; Misra, Srikant; Kumar, Rangu Seshu; Bajaj, Mohit; Blazek, Vojtech (iScience, 2025)
Demand-side management (DSM) enhances distribution network efficiency by shifting or reducing loads, alleviating network stress. The Load Shifting Policy (LSP) reallocates flexible loads to low-price periods without altering total demand, while the Load Curtailing Policy (LCP) incentivizes consumers to reduce peak demand. This study introduces a hybrid DSM approach that combines LSP and LCP with a smart charging strategy for plug-in hybrid electric vehicles (PHEVs). Using the hybrid load shifting and curtailment policy (HLSCP), the microgrid (MG) load profile was optimized, reducing generation costs from 707¥ for the base load to 682¥ with HLSCP and 676¥ when incorporating smart PHEV charging. Emissions decreased correspondingly, from 1267kg to 1246kg. These results demonstrate the hybrid DSM's capacity to tackle economic and environmental challenges in power systems. The Differential Evolution (DE) optimization method further validated the robustness and efficiency of this cost-effective, sustainable microgrid management approach.
Keywords: Energy Resources; Energy engineering; Energy systems; Environmental policy